p56lck interacts via its src homology 2 domain with the ZAP-70 kinase. - Duplay, P; Thome, M; Hervé, F; Acuto, O (1994)
p56lck, a member of the src family of protein tyrosine kinases, is an essential component in T cell receptor (TCR) signal transduction. p56lck contains a src homology 2 (SH2) domain found in a number of proteins involved in intracellular signaling. SH2 domains have been implicated in protein-protein interactions by binding to sequences in target proteins containing phosphorylated tyrosine. Using an in vitro assay, we have studied specific binding of tyrosine-phosphorylated proteins to a recombinant p56lck SH2 domain. In nonactivated Jurkat cells, two tyrosine-phosphorylated proteins were detected. Stimulation with anti-CD3 monoclonal antibodies induced the binding of seven additional tyrosine-phosphorylated proteins to the SH2 domain of p56lck. We have identified the zeta-associated tyrosine kinase, ZAP-70, as one of these proteins. Evidence suggests that binding of ZAP-70 to p56lck SH2 is direct and not mediated by zeta. The significance of this interaction was further investigated in vivo. p56lck could be coprecipitated with the zeta/ZAP-70 complex and conversely, ZAP-70 was detected in p56lck immunoprecipitates of activated Jurkat cells. The physical association of p56lck and ZAP-70 during activation supports the recently proposed functional cooperation of these two tyrosine kinases in TCR signaling.